Pemanfaatan Selulosa Ampas Tebu Sebagai Bahan Baku Dalam Pembuatan Bioplastik Berbasis Pati Umbi Talas - Mawar, Mawarni; Daulay, Abdul Halim; Husnah, Miftahul (Rekayasa Material, Manufaktur dan Energi, 2026)
Synthetic plastics are made from materials that come from petroleum. These materials do not break down easily and are not affected by chemicals or microbes. Because of this, they last a long time and are hard to get rid of in the environment. Most of these plastics are used only once, which causes a lot of waste over time. It can take up to 1,000 years for these plastics to break down on their own. This study looked at using cellulose from sugarcane bagasse as a material added to bioplastics made from taro starch. Glycerol was used to make the plastic more flexible. Different amounts of cellulose (0 g, 0.5 g, 1 g, and 1.5 g) were mixed with 5 g of taro starch and 2 ml of glycerol. The mixture was then dried. The bioplastics were tested for water absorption, how well they break down, how strong they are, how much they stretch, and their chemical structure using FTIR analysis. The results showed that adding cellulose changed the bioplastics' properties. More water was absorbed, they became stronger and more stretchy, but they broke down less. The best results came when 1.5 g of cellulose was added. This gave a tensile strength of 1.54 MPa, which meets the ASTM E8M standard, and an elongation of 66.7%, which meets the ASTM D882-12 standard. Overall, mixing taro starch with sugarcane bagasse cellulose made better bioplastics, especially in terms of strength and stretch, although the rate at which they break down was lower.